Utilization of Breed Chicken Eggshells for Biodiesel Preparation from Waste Cooking Oil - Rodhiansyah Djayasinga; Andi Setiawan; Agus Purnomo; Ardian Zakaria Amien; Hartanti Hartanti (Journal of Multidisciplinary Applied Natural Science, 2022)
Chicken eggshell waste is a promising source of CaO which can be converted into heterogeneous catalyst materials. The purpose of this study was to utilize CaO heterogeneous catalyst derived from breed chicken eggshell to produce biodiesel from waste cooking oil through the transesterification process. A total of 4 g of catalyst material was mixed with 200 g of waste cooking oil and 60 g of methanol, and then the mixture was stirred at a speed of 700 rpm for 6 h at 60 ± 40C. The produced biodiesel was analyzed using GC-MS to elucidate the various methyl ester compounds. The produced biodiesel was found to have a density of 855 kg/m3, viscosity of 3.74 mm2/s (cSt), and flash point of 135 0C. Based on these results, it can be concluded that breed chicken eggshells are potential sources for the preparation of CaO catalyst material to produce biodiesel from waste cooking oil. This finding is very useful for further optimization of mass catalysts heterogeneous CaO from breed chicken eggshells including the commercial production of biodiesel.